Adrenal, Alacrimal, Achalasia Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The results of a British and European Paediatric Endocrinology Society, multicenter collaborative, questionnnaire study of the neurological complications of familial glucocorticoid deficiency syndrome are reported from the Hospital for Sick Children, Great Ormond Street, London.